CONTROL SYSTEM USING LIGHT MEDIA INFORMATION LINE TELEPHONE - Yulikarnain Syam; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
Human mobility is higher, so that almost all activities conducted outside the home.By utilizing the phone lines, home or office lighting systems can be controlled fromelsewhere during a phone facilities. This tool makes it easy for users to turn on orturn off the lights.By using the DTMF receiver, this tool will work if you've heard a dial tone with thetelephone receiver, where the receiver can generate a unique frequency, so thelighting can be controlled.Telephone frequencies generated will be converted into binary, which is thenconnected to the controller circuit of RS flip flop loads and relays.